Adolescent Alcohol Use in Spain: Connections with Friends, School, and Other Delinquent Behaviors - Goldberg-Looney, Lisa D.; Sánchez-SanSegundo, Miriam; Ferrer-Cascales, Rosario; Albaladejo-Blazquez, Natalia; Perrin, Paul B. (Frontiers in Psychology, 2016)
This study examined the connections between adolescent alcohol use in Alicante, Spain and variables reflecting academic problems, potentially delinquent behaviors, friends’ alcohol consumption, and friendship quality. Information about alcohol use and a number of school and social variables was collected from adolescent students (N = 640) who completed the National Students School-Based Drug Survey in a classroom setting. Results suggested that gender was not significantly associated with alcohol use. Alcohol use increased with age and was more likely for adolescents enrolled in public schools in comparison to private. Academic problems explained 5.1% of the variance in adolescents’ alcohol use, potentially delinquent behaviors explained 29.0%, friends’ alcohol use 16.8%, and friendship quality 1.6%. When all unique predictors from these four models were included in a comprehensive model, they explained 32.3% of the variance in adolescents’ alcohol use. In this final model, getting expelled, participating in a fight, going out at night, the hour at which one returns, and the number of friends who have consumed alcohol were uniquely and positively associated with adolescents’ alcohol use. These results provide important information about multi-system influences on adolescent alcohol use in Alicante, Spain and suggest potential areas of focus for intervention research.